2016
DOI: 10.3847/2041-8205/824/2/l24
|View full text |Cite
|
Sign up to set email alerts
|

iPTF SEARCH FOR AN OPTICAL COUNTERPART TO GRAVITATIONAL-WAVE TRANSIENT GW150914

Abstract: The intermediate Palomar Transient Factory (iPTF) autonomously responded to and promptly tiled the error region of the first gravitational-wave event GW150914 to search for an optical counterpart. Only a small fraction of the total localized region was immediately visible in the northern night sky, due both to Sun-angle and elevation constraints. Here, we report on the transient candidates identified and rapid follow-up undertaken to determine the nature of each candidate. Even in the small area imaged of 126 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
(46 reference statements)
2
39
0
Order By: Relevance
“…We can now relate our model predictions with ongoing surveys such as iPTF (Kasliwal et al 2016) and Pan-STARRS . These are typically conducted in the r band, reaching limiting magnitudes of ∼ 20 − 21.…”
Section: Follow-up Of Ligo Triggersmentioning
confidence: 99%
See 1 more Smart Citation
“…We can now relate our model predictions with ongoing surveys such as iPTF (Kasliwal et al 2016) and Pan-STARRS . These are typically conducted in the r band, reaching limiting magnitudes of ∼ 20 − 21.…”
Section: Follow-up Of Ligo Triggersmentioning
confidence: 99%
“…However, note that the current LIGO configuration can detect NSNS mergers only out to 75 Mpc (Martynov et al 2016). For such a distance, the wind model would be easily detected by the search such as that by , and also the more optimistic dynamical ejecta models (e.g., N5 MNmodel2 DZ31) could be detected by ZTF (Kasliwal et al 2016) if nearby enough. With the rate of such events assumed above, we would expect about one such event per year, and not all may be observable by optical telescopes.…”
Section: Follow-up Of Ligo Triggersmentioning
confidence: 99%
“…No GRB-like afterglow was found in X-rays with Swift XRT (Evans et al 2016) or MAXI (N. Kawai et al, in preparation), in UV/optical with Swift UVOT (Evans et al 2016), or at GeV energies with Fermi LAT (Fermi-LAT Collaboration 2016). Tiled observations with wide-field optical instruments listed in Table 1 found many transients, but spectroscopy with the instruments listed in Table 2 along with further photometry showed that none of them were associated with GW150914 (Kasliwal et al 2016;Smartt et al 2016;Soares-Santos et al 2016;Morokuma et al 2016). Annis et al (2016) used DECam to search for a missing supergiant in the LMC, which would have been evidence for the collapse of a massive star that could have produced GWs, but failed to produce a typical corecollapse SN.…”
Section: Follow-up Observationsmentioning
confidence: 99%
“…Candidate classification, comparison of redshift with the GW distance, and use of source age are crucial constraints to rule candidates in and out. Detailed discussions of candidate selection, spectroscopic and broadband follow-up are presented in survey-specific publications about iPTF candidates (Kasliwal et al 2016) and about PESSTO follow-up of Pan-STARRS1 candidates (Smartt et al 2016). Notes.…”
mentioning
confidence: 99%
“…Rana et al 27 developed an enhanced scheduling algorithm that increases the odds of discovering an EM counterpart from a ground-based survey. This algorithm is being used by the iPTF group for scheduling follow-up observations 28 , and also being adapted for a radio searchs using the Jansky Very Large Array.…”
Section: Follow-up In Indiamentioning
confidence: 99%